Field evaluation of a coproantigen enzyme-linked immunosorbent assay for diagnosis of canine echinococcosis in a rural Andean village in Peru - Lopera L. (2003)
This study was funded by Consejo Nacional de Ciencia y Tecnolog ??a (CONCYTEC).We wish to thank Dr. Peter Schantz for manuscript review and the people and authoritiesof the farming cooperative of Tupac Amaru in Junin, Peru.